Ultra-high irradiance (UHI) blue light treatment: A promising method for inactivation of the wine spoilage yeast Brettanomyces bruxellensis - Grangeteau, C.; Lebleux, M.; David, V.; Rousseaux, S.; Alexandre, H.; Beney, L.; Dupont, S. (Food science & technology, 2024)
Ultra-high irradiance (UHI) blue light treatment is effective within minutes for inactivating both planktonic and sporicidal forms of numerous microorganisms. This treatment could represent a cost-effective and rapid process for microbial inactivation in a wide range of applications. Our study examined the effects of UHI blue light on planktonic and biofilm forms of Brettanomyces bruxellensis, one of the main spoilage microorganisms in red wines. Treatments of 1–5 min (22.2–111 J/cm2) were applied to planktonic cells, and 1–10 min (22.2–222 J/cm2) to biofilms. After treatments, we analyzed yeast cultivability and viability (esterase activity) using flow cytometry. The results showed that UHI blue light can inactivate both planktonic and biofilm forms of B. bruxellensis on wood or stainless steel. Treatments under 10 min led to a loss of cultivability with a lesser impact on viability, while a 10-min treatment caused complete loss of viability in all biofilms studied. Thus, UHI blue light treatment appears particularly promising for eliminating Brettanomyces biofilms on surfaces in the wine industry. •Brettanomyces bruxellensis is one of the main spoilage microorganisms in red wines.•UHI LED-based treatments inhibit planktonic and biofilm forms of B. bruxellensis.•Short UHI treatments resulted in VBNC state of cells.•UHI treatment for 10 min resulted in complete loss of cell viability in biofilms.